ENGLISH TEACHERS’ STRATEGIES IN GIVING ORAL CORRECTIVE FEEDBACK ON STUDENTS’ SPEAKING PERFORMANCE - Widia Siska; Mukhaiyar Mukhaiyar; Ratmanida Ratmanida (Proceedings of ISELT FBS Universitas Negeri Padang, 2018)
The aims of this research were to analyze the strategies used by the English teachers in giving corrective oral feedback on students’ speaking performanceand the reasons of the English teachers tend to use particular strategies in giving oral corrective feedback on students’ speaking performance at SMAN 1 Koto Salak and SMAN 2 Koto Baru. The type of this research was descriptive qualitative research. The data were collected through video recorder and interview. The sources of data were 6 English teachers at SMAN 1 Koto Salak and SMAN 2 Koto Baru Dharmasraya. The finding of this research indicated that oral corrective feedback strategies used by the teachers were explicit correction, recast, clarification request, metalinguistic clue, elicitation, repetition, body language and combined strategies. The strategies that mostly used by the English teachers were recast and explicit correction. The teacher tend to used particular strategies because they know the level of the students’ understanding, motivation, condition, and the ability in understanding and receiving what the teacher gave